Mapping of Syphilis Cases Using Geographic Information System (GIS) in Denpasar City in 2024 - I Wayan Laksamana Putra Adinatha; Nyoman Ngurah Adisanjaya; Rai Riska Resty Wasita; Putu Okta Wijayanti (Publikasi Indonesia, 2025)
Cases of sexually transmitted infections (STIs), especially syphilis, continue to show an increase in various regions of Indonesia, including Denpasar City. This disease not only causes serious medical impacts but also has implications for social aspects and community productivity. This study was conducted with the aim of describing the distribution pattern and classifying syphilis cases in Denpasar City in 2024 through a Geographic Information System (GIS) approach. The study used a quantitative method with a descriptive design. Secondary data analyzed amounted to 297 cases, obtained from the Denpasar City Health Office and the Kerti Praja Foundation, with a research sample of 170 cases based on the calculation of the Slovin formula. Patient location points were determined through address data converted to GPS coordinates, then processed using ArcView 3.3 software to produce distribution maps and classification of cases using the Kingma method. The results indicated that there were 170 cases of syphilis in four regions. The most cases were recorded in South Denpasar with 85 (high category), followed by West Denpasar with 52 (medium category), while North Denpasar had 22 cases and East Denpasar had 11 (low category). The majority of cases were found in the productive age group of 26-45 years, followed by the age group of 12-25 years. In addition, the number of cases occurred more in men (136 cases) than women (34 cases). This mapping is expected to serve as a basis for developing more targeted prevention strategies and health interventions, especially for productive and vulnerable age groups.